Constructing the Code Description Of the Transformant DCT Taking into Account their Structural Features - Barannik, N.; Tverdokhlib, V.; Eliseev, E.; Zakomorna, K.; Vorontsova, N.; Shmakov, V. (IEEE, 2020)
An approach to the construction of a code description of DCT transformants, taking into account the structural features of their binary representation, is presented. It is shown that the proposed model for constructing the code has the ability to reduce the initial number of bits, and also allows you to form a code description of the transformant by a set of independent code blocks. This makes it possible to use this coding method in a video bit rate control system.
Keywords: bit-plane; binary transformant representation; bit-rate; DCT-transformant; data compression; codeword; video processing